Remoción de cromo hexavalente de un lixiviado industrial utilizando un composito biocarbon-nanopartícula e impacto de las nanopartículas de Cerio en el tratamiento de aguas residuales (Jóvenes en la Ciencia, 2024)
chromium (Cr (VI)) from industrial leachates. The physicochemical characterization of the leachate wasperformed, along with the determination of the maximum Cr (VI) removal using adsorption isotherms.Additionally, an impregnation method with γ-Fe2O3 nanoparticles was applied. The hypothesis thatimpregnation would enhance Cr (VI) removal was confirmed, showing that impregnated biochar achievedsignificantly higher removal compared to non-impregnated biochar.